Anomali Pangkal Arteri Koroner: Peran CT Angiografi - Isyana M Kurniawan; Elen Elen; Celly A Atmadikoesoemah; Manoefris Kasim (The Indonesian Heart Association, 2014)
Introduction: The anomalous origin of the right coronary artery (RCA) from the left coronary sinus coursing between the aorta and the pulmonary trunk is rare, but may cause myocardial ischemia and sudden death. Multislice CT coronaryangiography offers the possibility to visualize anomalous coronary artery origin non-invasively in details.Case Illustration: A 54-year-old man with a history of arterial hypertension, and hypercholesterolemia began to present with typical chest pain. After some non-invasive examination, he had coronary angiographythat revealed 70% stenosis at mid intermediate artery, normalLMCA, LAD and LCX. Ostium of RCA was found near the left valsava sinus afterrepeated cannulation attempts, no stenosis was found at RCA. After successful revascularization at intermediate artery, patient still had typical chest pain with positive ischemic response in treadmill test. Multislice CT coronary angiography was performedto evaluate the etiology of chest pain. The scan showed patent stent at intermediate artery and anomalous RCA origin from the left coronary sinus withacute angle take-off, luminal narrowing of the osteal-proximal part, as well as luminal compression between the ascending aorta and the pulmonary trunk (an interarterial course) while RCA appeared as dominant vessel. These features were considered as malignant coronary anomaly that could lead to the recommendation of surgical correction.Discussion: Accurate recognition and documentation of coronary artery anomalies are essential to determine the significance of such findings and to avoid furtherclinical complications. Multislice CT coronary angiography is a non-invasive imaging modality that can easily and precisely depict the origin and course of coronary artery anomalies as well as its relationship with adjacent structures.